User Satisfaction and Challenges in Telemedicine Services during the COVID-19 Pandemic in Indonesia: A Population-Based Analysis - Adinda, Havivi Rizky; Syakurah, Rizma Adlia; Pariyana, Pariyana (Journal of Health Policy and Management, 2024)
Background: The COVID-19 pandemic has led to a surge in telemedicine utilization in Indonesia, necessitating increased attention toward user satisfaction and encountering obstacles in telemedicine services. This study aims to analyze the satisfaction and barriers faced by users of telemedicine applications, considering population characteristics during the COVID-19 pandemic in Indonesia. Subjects and Method: Using a descriptive observational design with a cross-sectional approach, the study encompassed the entire population of telemedicine users during the COVID-19 pandemic, with samples adhering to predetermined inclusion and exclusion criteria. Data were collected through Google Forms questionnaires from August 2020 to November 2020. Subsequently, data were subjected to chi-square tests (alternative: Kruskal-Wallis) and logistic regression analyses, with p-value<0.05 and 95% confidence interval. User satisfaction with telemedicine was associated with factors such as domicile, settlement, provider, health insurance, and utilized internet network (p<0.05). Results: User satisfaction with telemedicine was associated with factors such as domicile, settlement, provider, health insurance, and utilized internet network (p<0.05). Conversely, barriers encountered in telemedicine exhibited associations with gender, marital status, age, regional origin, residence, education, occupation, health insurance, income, provider type, internet network, and internet quota (p<0.05). A significant correlation was observed between barriers and user satisfaction with telemedicine (p<0.001). The most influential factor affecting satisfaction was income less than Rp 1,500,000 per month (OR 30.818; 95% CI: 1.751-542.394), while pay ranging from Rp 3,500,000 to 5,500,000 per month exhibited the most substantial impact on barriers (OR 5.266; 95% CI: 2.326-11.920). Conclusion: Most respondents expressed satisfaction and encountered no obstacles when employing telemedicine. Respondents suggested enhancing telemedicine usage by emphasizing the importance of diagnostic accuracy, simplifying processes, maintaining confidentiality, optimizing application features, and improving network speed.